Dissecting limiting factors of the Protein synthesis Using Recombinant Elements (PURE) system. Issue 1 (2nd January 2017) - Li, Jun; Zhang, Chi; Huang, Poyi; Kuru, Erkin; Forster-Benson, Eliot T. C.; Li, Taibo; Church, George M.
ABSTRACT: Reconstituted cell-free protein synthesis systems such as the Protein synthesis Using Recombinant Elements (PURE) system give high-throughput and controlled access to in vitro protein synthesis. Here we show that compared with the commercial S30 crude extract based RTS 100 E. coli HY system, the PURE system has less mRNA degradation and produces up to ∼6-fold full-length proteins. However the majority of polypeptides PURE produces are partially translated or inactive since the signal from firefly luciferase (Fluc) translated in PURE is only ∼2/3 rd of that measured using the RTS 100 E. coli HY S30 system. Both of the 2 batch systems suffer from low ribosome recycling efficiency when translating proteins from 82 kD to 224 kD . A systematic fed-batch analysis of PURE shows replenishment of 6 small molecule substrates individually or in combination before energy depletion increased Fluc protein yield by ∼1.5 to ∼2-fold, while creatine phosphate and magnesium have synergistic effects when added to the PURE system. Additionally, while adding EF-P to PURE reduced full-length protein translated, it increased the fraction of functional protein and reduced partially translated protein probably by slowing down the translation process. Finally, ArfA, rather than YaeJ or PrfH, helped reduce ribosome stalling when translating Fluc and improved system productivity in a template-dependent fashion.